2017
DOI: 10.1111/his.13160
|View full text |Cite
|
Sign up to set email alerts
|

Well‐differentiated invasive breast cancers with equivocal HER2 immunohistochemistry: what is the yield of routine reflex in‐situ hybridization testing?

Abstract: The rate of HER2 amplification among well-differentiated breast cancers is very low. Basolateral staining in well-differentiated tumours may be overinterpreted as HER2 IHC 2+, but is rarely associated with HER2 amplification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Commonly used tests include immunohistochemistry (IHC), [92] fluorescence in situ hybridization (FISH), [93] or comparative genomic hybridization (CGH). [94] IHC exploits the principle of antibodies conjugated with enzymes for the specific binding to the antigens in biological tissues.…”
Section: Melanoma Diagnosis and Detection Methodsmentioning
confidence: 99%
“…Commonly used tests include immunohistochemistry (IHC), [92] fluorescence in situ hybridization (FISH), [93] or comparative genomic hybridization (CGH). [94] IHC exploits the principle of antibodies conjugated with enzymes for the specific binding to the antigens in biological tissues.…”
Section: Melanoma Diagnosis and Detection Methodsmentioning
confidence: 99%
“…The activation of the mitogen-activated protein kinase (MAPK) and the phosphatidylinositol 3 kinase-protein kinase B (PI3K-Akt) pathways due to HER2 homo- or hetero-dimerisation promotes tumour cell proliferation, differentiation, survival and migration, causing adverse pathological disease and poor prognosis [ 27 , 32 , 33 ]. Biological responses of the activated signalling pathways are precisely dependent on the ligands involved and dimers formed; thus, dysregulation of HER receptors can result in aberrant signalling, leading to fundamental biological processes to be altered [ 34 , 35 , 36 ]. Moreover, cell polarity and adhesion are specifically disrupted by HER2 activation, which can cause aberrant asymmetric cell division and subsequent overgrowth of less differentiated cells [ 37 , 38 ].…”
Section: Her2 Breast Cancermentioning
confidence: 99%
“…This process occurs through the binding of the Par6 and atypical protein kinase C (Par6-aPKC) components of the Par complex upon HER2 activation [ 37 ]. Thus, HER2(+) tumours are poorly differentiated [ 36 , 39 ]. Amplification of the HER2 gene, located on chromosome 17 (17q12q21), leads to the overexpression of HER2 receptors and is highly associated with increased cell proliferation, tumorigenesis and invasion, resulting in distant metastases [ 33 , 40 ].…”
Section: Her2 Breast Cancermentioning
confidence: 99%
“…HER2/neu amplification has been associated with a poor prognosis due to the activation of the growthsignaling pathway that leads to tumor cell proliferation. Trastuzumab and other anti-HER2/neu therapies have been proven to be an effective treatment for HER2/neu positive breast cancer patients [3]. Screening programmes for HER2/ neu expression in breast carcinoma patients has also been proven to reduce the cost of therapy [4].…”
Section: Introductionmentioning
confidence: 99%
“…A study on the impact of these modified cut-offs revealed a 2% increase in overall HER2/neupositivity at their institution [5]. Current guidelines recommend testing for HER2/neuamplification for all invasive breast cancers with fluorescence in situ hybridization that are equivocal on immunohistochemical analysis [3].…”
Section: Introductionmentioning
confidence: 99%